Impact of Land Use Change to Dependable Flow in Kuncir River, Nganjuk District, East Java - Liyantono .; Fajardo .; Tasuku Kato (Jurnal Keteknikan Pertanian, 2017)
AbstractCurrently, Kuncir River is a source of irrigation water in the southern of Nganjuk District. The potential ofKuncir River was assessed by measuring the dependable flow as an indicator of water supply for irrigatedareas. The objective of this study was to estimate the river discharge and its dependable flow for irrigationfrom Kuncir River in Nganjuk District. River discharge data was collected from Kuncir River, rainfall data wascollected from Nganjuk District, East Java and climate data was collected from climatology station of BadanMeteorologi Klimatologi dan Geofisika (BMKG) Sawahan, Nganjuk. There were two major steps on thisstudy which were model development and model simulation using SWAT after calibration and validation.Model simulation showed NS value of 0.67 with mean daily flow of 7.15 m3 s-1. Based on land use changescenario, the conversion of 50% on forest and 50% on range-grasses into agriculture land could increase3.1% and 2.5% of average river discharge, respectively.AbstrakSungai Kuncir merupakan sumber air irigasi di bagian selatan Kabupaten Nganjuk. Potensi SungaiKuncir dapat dikaji melalui perhitungan debit andalan untuk dijadikan indikator jumlah pemenuhan air didaerah irigasi. Penelitian ini bertujuan menduga debit air sungai dan menghitung besar debit andalanuntuk irigasi pada Sungai Kuncir, Kabupaten Nganjuk. Data debit sungai dikumpulkan langsung di SungaiKuncir, data hujan dikumpulkan dari Dinas PU dan Pengairan Kabupaten Nganjuk, Jawa Timur, dan dataiklim dikumpulkan dari stasiun kimatologi Badan Meteorologi Klimatologi dan Geofisika (BMKG) Sawahan,Nganjuk. Penelitian dilakukan melalui dua tahap, yaitu proses pembangunan model dan proses simulasidengan SWAT setelah melalui proses kalibrasi dan validasi. Simulasi model memiliki nilai NS sebesar 0.67dan debit rata-rata harian sebesar 7.15 m3 s-1. Skenario perubahan lahan menggambarkan konversi 50%lahan hutan dan 50% semak belukar menjadi lahan pertanian berpotensi meningkatkan nilai debit rata-rataSungai Kuncir masing-masing sebesar 3.1% dan 2.5%.